(untitled) (Asian Journal of Medical and Biological Research, 2016)
Malathion is an organophosphorous insecticide widely used in the agricultural field in Bangladesh and reach in the aquatic environment through rain wash. In the present study, we examined the effects of Malathion on hematological parameters and gills morphology in common carp exposed to two sub-lethal concentrations (1.5 and 3.0 mg/L) for a period of 192h (8 days). For hematological parameters fish were sacrificed at 24, 48, 72, and 96h after start of exposure. Gills were collected at 192h after start of exposure. The blood glucose level was significantly elevated with increasing the concentration of Malathion. Red blood cells (RBCs), hemoglobin (Hb) and hematocrit (Hct) values were significantly decreased after the exposure of Malathion. Significant increments were observed in case of the mean corpuscular volume (MCV) and mean corpuscular hemoglobin concentration (MCHC), while no distinct changes were noted for mean corpuscular hemoglobin (MCH). Interestingly, white blood cells (WBCs) count was significantly increased with toxicity of Malathion. Several morphological changes, such as telangiectasia, blood lamellar congestion, hypertrophy of filaments, lamellar fusion were observed in the gills of fish exposed to Malathion. The present study revealed that the insecticide had adverse effects on various blood parameters and gills morphology in common carp. Thus, the use of insecticide in the agriculture field may be a threat to fauna and flora of the aquatic environment. Asian J. Med. Biol. Res. September 2016, 2(3): 370-378